2010
DOI: 10.1053/j.gastro.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Pancreatic Cystic Neoplasms: Maximizing Survival and Quality of Life Using Markov-Based Clinical Nomograms

Abstract: Background-The natural history and management of pancreatic cysts, especially for branch duct intraductal papillary mucinous neoplasms (BD-IPMNs), remains uncertain. We developed evidencebased nomograms to assist with clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 75 publications
1
53
0
5
Order By: Relevance
“…In tumors with a diameter Ͻ2 cm, malignancy is rare in the absence of additional typical radiographic findings. In an attempt to stratify the indication for surgery in BD-IPMN by age and quality of life, Weinberg and coworkers conducted a Markov-based clinical nomogram for BD-IPMN of the pancreatic head [97]. They revealed that, for patients merely focusing on longest survival, regardless of quality of life, all BD-IPMNs Ͼ2 cm should be surgically removed.…”
Section: Prediction Of Malignancy In Ipmnmentioning
confidence: 99%
“…In tumors with a diameter Ͻ2 cm, malignancy is rare in the absence of additional typical radiographic findings. In an attempt to stratify the indication for surgery in BD-IPMN by age and quality of life, Weinberg and coworkers conducted a Markov-based clinical nomogram for BD-IPMN of the pancreatic head [97]. They revealed that, for patients merely focusing on longest survival, regardless of quality of life, all BD-IPMNs Ͼ2 cm should be surgically removed.…”
Section: Prediction Of Malignancy In Ipmnmentioning
confidence: 99%
“…Some patients present symptoms at the time of diagnosis (7-43%), being more frequent the presence of abdominal pain, jaundice, and previous history of pancreatitis.Othersymptomsareasfollows:weightloss,nauseaorvomiting,anddiabetes [5,6,27].…”
Section: Symptomsmentioning
confidence: 99%
“…These factors support a conservative management with follow-up in patients who do not have risk factors predicting malignancy. Younger patients (<65 years) with a cyst size of>2cmmaybecandidatesforresectionowingtothecumulativeriskofmalignancy [27].…”
Section: Positivecytologyoneus-guidedfnahasthehighestspecificityfordimentioning
confidence: 99%
“…However, for the same age group (85 years and older) stopping surveillance is also favored for any pancreatic cyst size irrespective of any operative risk approach, when the primary interest is improving quality-adjusted survival. Th is is likely due to the poor quality of life experienced postoperatively oft en outweighing the minimal benefi t derived from surgical resection in this population ( 6 ).…”
mentioning
confidence: 99%
“…While their study did confi rm a very high disease specifi c survival of 98.6% for BD-IPMNs without WF/ HRS on long-term surveillance at 12 years (as has been seen in other studies), the most startling fi nding is that 26(18%) patients under surveillance in this study developed either WF or HRS during surveillance beyond 5 years. Th e authors argue that their data ing overall survival and quality of life ( 6 ). Using these models, surgery is the preferred strategy for patients who value overall survival regardless of quality of life for any cyst size greater than 2 cm even aft er considering the possibility that the cyst is not malignant.…”
mentioning
confidence: 99%